Acute Release of Tissue Factor Pathway Inhibitor after In Vivo Thrombin Generation in Baboons - Lupu, Cristina; Kruithof, Egbert K. O.; Kakkar, Vijay V.; Lupu, Florea (Thrombosis and Haemostasis, 1999)
Tissue factor pathway inhibitor (TFPI), the major downregulator of the procoagulant activity of tissue factor (TF), is synthesised by endothelial cells (EC) and acutely released in vitro after thrombin stimulation. Expression of TF on EC and subsequent thrombin generation occurs in vivo during sepsis or malignancy, inducing disseminated intravascular coagulation (DIC). The present study investigates the changes in plasma TFPI in relation to markers of in vivo thrombin generation induced by injection of factor Xa (FXa)/phospholipids in baboons at dosages leading to partial (48%) or complete fibrinogen depletion. The plasma concentrations of thrombin-antithrombin III (TAT) and fibrinopeptide A (FpA), as markers of in vivo generation of thrombin, were strongly enhanced after injection of FXa/phospholipids. TFPI levels, whether measured as antigen or activity, increased significantly in both treatment groups within few minutes, and were dependent on the dose of FXa/phospholipids. Significant positive correlations between plasma levels of TFPI and of TAT or FpA were observed. Altogether, our results indicate that experimentally induced in vivo generation of thrombin causes the acute release of TFPI, high-lighting a possible novel function of thrombin in downregulation of the coagulation process, potentially relevant for the outcome of DIC.
Keywords: TFPI; thrombin; DIC; non-human primate; animal model